Meningkatkan Keterampilan Cara Menggunting Rambut Melalui Pembelajaran Individual bagi Anak Tuna Rungu - Artati - - (Jurnal Penelitian Pendidikan Khusus, 2014)
This research was conducted at SLB Binar Tarusan. The study uses action research class. Subject of this research is a deaf student at VII grade. The problem of this research accordance with the way cutting the hair skill on the deaf. Where this skill has a vital on deaf in the future after school. The problem occure that the kid has difficulties in understanding the way to cut the hair of oval model rightly. So, the researcher try the kid to give the skill with using individual learning program. The aim of the research was to know the process to execute the learning the skill the way to cut the hair. Oval model through individul learning and prove whether using individual learning and increase ability in cutting the hair oval model in deaf kid. The result finding to increasing the skill the way to cut the hair through individual learning on deaf kid gotten that becoming increase from cycle I to cicle II. Based on the first  and second meeting on cicle I with collaborated with teacher class, so found that the first meeting of the kid in 40% and at second meeting increase abiliy of becoming 60%. The researcher goes on to second cycle. On second meeting increase becoming 100%. It means that the kid has able in execute in cutting hair oval model and this research finished in second cicle.